A comparative study of single-vs. double-row technique in surgical treatment of insertional Achilles tendinopathy - Maciel, Ricardo; Castilho, Rodrigo; Baumfeld, Daniel; Baumfeld, Tiago (Journal of the Foot & Ankle, 2021)
Objective: This retrospective study compared the clinical and functional results of single- and double-row surgical techniques for insertional Achilles tendinopathy in the postoperative period. Methods: In this case series, 29 patients who underwent surgery with one of the two techniques were followed up for one year postoperatively. Data were collected from medical records, imaging exams, and visual analog scale (VAS), Victorian Institute of Sports Assessment-Achilles (VISA-A) questionnaire, 12-item Short Form Health Survey (SF-12), and Foot and Ankle Ability Measure (FAAM) scores. Results: The following mean values (5% significance level) were found for single- and double-row techniques, respectively: postoperative VAS (2.9/2.2), FAAM-ADL (71.9/74.4), FAAM-Sports (28.3/29.8), SF-12 physical component (45.2/47.0), SF-12 mental component (44.9/48.2), and VISA-A (72.1/75.9). The complication rate did not differ significantly between the techniques. Conclusion: No significant differences were found in any of the scores between the two surgical techniques. Level of Evidence III; Therapeutic Studies, Comparative Retrospective Study.